2016
DOI: 10.1016/j.molcel.2015.12.024
|View full text |Cite|
|
Sign up to set email alerts
|

Regulated Formation of lncRNA-DNA Hybrids Enables Faster Transcriptional Induction and Environmental Adaptation

Abstract: Summary Long non-coding (lnc)RNAs, once thought to merely represent noise from imprecise transcription initiation, have now emerged as major regulatory entities in all eukaryotes. In contrast to the rapidly expanding identification of individual lncRNAs, mechanistic characterization has lagged behind. Here we provide evidence that the GAL lncRNAs in the budding yeast S. cerevisiae promote transcriptional induction in trans by formation of lncRNA-DNA hybrids or R-loops. The evolutionarily conserved RNA helicase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
105
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 69 publications
(137 reference statements)
3
105
1
Order By: Relevance
“…Consistently, the GAL lncRNAs have no effect on induction from the derepressed (Craffinose) state, but rather confer a specific fitness advantage to yeast cells over those lacking the GAL lncRNAs during a glucose to galactose switch. 48,53 GAL lncRNA-dependent induction occurs when the GAL lncRNAs are encoded in trans, indicating that lncRNA-dependent transcriptional induction and repression are mechanistically distinct. This result is reminiscent of Air (Airn), which also functions in mechanistically distinct cis and trans roles to regulate gene expression.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Consistently, the GAL lncRNAs have no effect on induction from the derepressed (Craffinose) state, but rather confer a specific fitness advantage to yeast cells over those lacking the GAL lncRNAs during a glucose to galactose switch. 48,53 GAL lncRNA-dependent induction occurs when the GAL lncRNAs are encoded in trans, indicating that lncRNA-dependent transcriptional induction and repression are mechanistically distinct. This result is reminiscent of Air (Airn), which also functions in mechanistically distinct cis and trans roles to regulate gene expression.…”
mentioning
confidence: 99%
“…74 Strikingly, nuclear depletion of Dbp2 using the "anchor away" strategy 75 resulted in time-dependent accumulation of R-loops beginning at the 5 0 end of GAL1 and spreading across GAL1, GAL10 and through the 3 0 end of GAL7. 53 Removal of the lncRNAs through genomic deletion reduced R-loops at the 5 0 end of GAL1 and abolished detection of these structures across the rest of the GAL cluster locus. This suggested that Dbp2 regulates formation of lncRNA R-loops at the GAL genes (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations